Analisis Pengaruh Kurs, Tingkat Inflasi, dan FDI terhadap Ekspor Ikan Tuna Indonesia ke Amerika Serikat Tahun 1990-2020 - Keren Hapukh Frederica Sasabone; Anak Agung Bagus Putu Widanta (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Exports are one of the main factors in a country's economic growth, including Indonesia. Indonesian tuna fish exports are one of the leading export commodities marketed in international trade and have a positive impact on the national economy. This research aims to analyze the simultaneous influence of the exchange rate, inflation rate, and FDI on Indonesian tuna exports to the United States and to analyze the influence of the exchange rate, inflation rate, and FDI partially on Indonesian tuna exports to the United States. The analysis technique used is multiple linear regression analysis. The results of data analysis show that the exchange rate, inflation rate and FDI simultaneously have a significant effect on the value of Indonesian tuna exports to the United States in 1990-2020. Partially, the exchange rate has a positive and significant effect on the value of Indonesian tuna exports to the United States. Meanwhile, the level of inflation and FDI do not have a negative and partially significant effect on the value of Indonesian tuna exports to the United States.